2019
DOI: 10.1139/cjpp-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 and -2 effects on glucose and lipid metabolism in white adipose tissue from fed and fasted rats

Abstract: Stanniocalcin-1 and -2 belong to a family of molecules that exhibit both paracrine and autocrine effects in mammalian cells. Human stanniocalcin-1 (hSTC-1) is expressed in a wide range of tissues, including white adipose tissue. In fed rats, hSTC-1 increases carbon flux from glucose to lipids in retroperitoneal white adipose tissue. Human stanniocalcin-2 (hSTC-2) is expressed in almost all tissues and regulates various biological processes. The aim of this work was to study the action of hSTC-1 and hSTC-2 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In liver, putative stanniocalcin receptor was present in hepatocytes as detected by punctate staining, especially on cell membranes near central vein (12). Therefore, based on the current immunological data, it is conceivable that STC2 is bound to the putative stanniocalcin receptor(s) and might function in an autocrine and/or paracrine fashion as speculated by various groups (5,6,12,44).…”
Section: Structure Expression and Distribution Of Stc2mentioning
confidence: 88%
See 1 more Smart Citation
“…In liver, putative stanniocalcin receptor was present in hepatocytes as detected by punctate staining, especially on cell membranes near central vein (12). Therefore, based on the current immunological data, it is conceivable that STC2 is bound to the putative stanniocalcin receptor(s) and might function in an autocrine and/or paracrine fashion as speculated by various groups (5,6,12,44).…”
Section: Structure Expression and Distribution Of Stc2mentioning
confidence: 88%
“…STC2 has also been involved in deregulation of glycaemia in obese mice as well as in type 2 diabetes mellitus patients (8). Additionally, it was speculated that STC2 might play role in glucose uptake and metabolism, glycogen storage and triacylglycerol synthesis in both brown and white adipose tissues (44,63). Taken together STC2 exhibits pro-survival effect in various model systems.…”
Section: Involvement In Cytoprotectionmentioning
confidence: 99%
“…Stanniocalcin is a secreted glycoprotein, originally studied in fish as hormone regulator of serum calcium levels (209). It is expressed in a wide range of tissues and regulates various biological processes including lipid and glucose metabolism (210,211), the growth hormone-insulin-like growth factor axis (212), as well as cellular calcium and phosphate homeostasis (213,214). STC2 is related to growth restriction (209) and organomegaly when overexpressed at the genetic level (215).…”
Section: Discussionmentioning
confidence: 99%
“…STC1, as well as STC2, was originally identified as a calcium/phosphate-regulating hormone. Recent studies have indicated that the STC-1 gene is closely related to glucose and lipid metabolism as well as to mitochondrial function [ 29 , 30 ]. In addition, PARP or PAR alterations have been described in tumors, specifically those influencing EMT [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%